Volunteering for a better future: A pilot Sustainability Ambassadors Training Program. (21st March 2022) - Solly, Kane; Smyer, Michael A.; Nichols, Kim; Steffens, Niklas K.; Kastelle, Timothy H.; Pachana, Nancy A.
Abstract: Objective: Older adults are an untapped resource for leading sustainability change. This study assessed a pilot study of a Sustainability Ambassadors Training Program for older adults. Methods: The pilot training program was conducted with a sample of 14 older adults over a single day, with some follow‐up activities for participants at home. Activities included completing a sustainable action card‐sorting activity measuring an individual's ability to make sustainable changes within their lives. A brief researcher‐devised empowerment scale was administered pre‐ and postworkshop. Results: Quantitative data revealed that sustainability empowerment increased from pre‐ to post‐training sessions and was related to the number of sustainability actions participants thought were achievable. Conclusions: The data suggest that such a brief training workshop can both yield personal change and potentially provide opportunities for a peer network to facilitate change within communities.